PENTAGON FRAUD MODELLING: HOW IT AFFECTS FINANCIAL STATEMENT - Fachrul Roza (ZILLZELL MEDIA PRIMA, 2024)
This study examined conceptually the detection of financial statement fraud using Banking fraud in Indonesia Stock Exchange (BEI) Companies Listed on the Indonesia Stock Exchange (BEI) during 2017-2021 in a total of 200 samples from 40 companies using Eviews analysis. The methodology adopted in this study is quantitative research in which relevant and extant literature related to elements in Pentagon fraud model is reviewed about financial statement fraud. Financial stability does not affect financial statements in a significant linear fashion, and financial targets and external parties that seek to suppress have a significant negative impact on financial statements and do not show significance on other variables, being the result of this study. Current fraud insights are an important factor, both for managers in managing finances and for regulators/policymakers in preventing structured and reliable financial statement fraud.